A 40-nm 169mW Ultrasound Imaging Processor Supporting Advanced Modes for Hand-Held Devices - Lo, Yi-Lin; Lo, Yu-Chen; Yang, Chia-Hsiang (IEEE transactions on biomedical circuits and systems, 2025)
Hand-held ultrasound devices have been widely used in the field of healthcare and power-efficient, real-time imaging is essential. This work presents the world's first ultrasound imaging processor supporting advanced modes, including vector flow imaging and elastography imaging. Plane-wave beamforming is utilized to ensure that the pulse repetition frequency (PRF) is sufficiently high for the advanced mode. The storage size and power consumption are minimized through algorithm-architecture co-optimization. The proposed plane-wave beamforming reduces the storage size of the required delay values by 43.7%. By exchanging the processing order, the storage size is reduced by 78.1% for elastography imaging. Parallel beamforming and interleaved firing are employed to achieve real-time imaging for all the supported modes. Fabricated in 40-nm CMOS technology, the proposed processor integrates 4.7M logic gates in core area of 3.24mm {}^{2} . This work achieves a 20.3 \boldsymbol{×} higher beamforming rate with 5.3-to-29.1 \boldsymbol{×} lower power consumption than the state-of-the-art design. It also has 60% lower hardware complexity (in terms of gate count), in addition to the capability for supporting the advanced mode.